PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS XII IPA SMAN 1 LENGAYANG KABUPATEN PESISIR SELATAN - Ella, Wanda Tarli; Aima, Zulfitri; Melisa, Melisa (Pendidikan Matematika, 2013)
Background of the research is the comprehension of mathematical concepts and low student activities. This research therefore aims to determine how studentsâ learning activities with the implementation of active learning strategies TheÂ  Power Of Two types and to determine whether studentsâ comprehension of mathematical concepts by applying active learning strategy types The Power Of Two is better than the studentsâ comprehension of mathematical concepts with the application of learning conventional class XII science student of SMAN 1 Lengayang school year 2013/2014. This type of research is experimental research. Population in this research is class XII science student of SMAN 1 Lengayang consisting of four classes. TheÂ  sampling technique is done randomly, which was selected as the sample classes are class XII science 1 as the experiments class and class XII science 2 as the control class. The instrument used in this study was the observation sheet and final test with indicator of comprehension of concept. Form of test used isÂ  a form of essay with a reliability test = 0,8322. Hypothesis testing use a t-test with the help of the software MINITAB. Based on the analysis of the data found P-value=0,033 is less than = 0,05, then this hypothesis is accepted. Thus concluded that the studentsâ comprehension of mathematical concepts with application of active learning strategies types The Power Of Two is better than the studentsâ comprehension of mathematical concepts with coventional learning in class XII science SMAN 1 Lengayang kabupaten Pesisir Sealatan.